2021
DOI: 10.4274/tao.2021.2021-4-17
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine Enhances the Balance System and Postural Balance in Short Time in Healthy Individuals

Abstract: Objective: This study aimed to explore the effects of caffeine on balance function by determining the extent to which caffeine consumption affects postural sway and balance control in healthy individuals. Methods: Thirty healthy participants aged 20–35 years without any vestibular disorder were enrolled in this study. The participants were randomly divided into two groups, and those in Group 1 were given two cups of regular coffee (300–350 mg) while those in Group 2 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…Although, according to our knowledge, there has not yet been a study evaluating caffeine effects on the balance and ambulatory performance of PwMS, previous studies have revealed caffeine’s potential benefits on balance and some aspects of gait performance in populations other than PwMS [ 28 30 , 62 , 63 ]. Notably, the results of these studies considerably vary by the study population’s age and sex.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although, according to our knowledge, there has not yet been a study evaluating caffeine effects on the balance and ambulatory performance of PwMS, previous studies have revealed caffeine’s potential benefits on balance and some aspects of gait performance in populations other than PwMS [ 28 30 , 62 , 63 ]. Notably, the results of these studies considerably vary by the study population’s age and sex.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the results of these studies considerably vary by the study population’s age and sex. A recent randomized clinical trial in 30 young adults (20–35 years, female: 50%) indicated that caffeine ingestion (300–350 mg) resulted in improvements in postural balance and motor control [ 28 ]. Another study on 25 healthy middle-aged women (50–60 years) reported a positive effect of caffeine ingestion (100 mg) on postural balance during different situations (i.e., with closed eyes on the foam surface) [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations